Neonatal Hyperoxic Exposure Persistently Alters Lung Secretoglobins and Annexin A1. (26th September 2013) - Raffay, Thomas M.; Locy, Morgan L.; Hill, Cynthia L.; Jindal, Nik S.; Rogers, Lynette K.; Welty, Stephen E.; Tipple, Trent E.
Abstract : Altered functions of the lung epithelial surface likely contribute to the respiratory morbidities in infants with bronchopulmonary dysplasia (BPD). Infants with BPD exhibit decreased expressions of secretoglobins (SCGBs), including Clara cell secretory protein (CCSP). Expression of lung SCGB and annexin A1 (ANXA1) is persistently altered in CCSP knockout mice suggesting that CCSP indirectly influences innate immune responses. The present studies tested the hypothesis that neonatal hyperoxic exposure induces deficits in CCSP expression that are associated with persistent alterations in lung SCGB and ANXA1 expression. Newborn C3H/HeN mice were exposed to room air (RA) or 85% O2 from birth and were sacrificed at 14 d or returned to RA for 14 d. Neonatal hyperoxia followed by RA recovery was associated with decreased lung CCSP and SCGB3A1 protein but not mRNA expression. Hyperoxia-induced alterations in the charge characteristics of ANXA1 were unchanged by RA recovery and were associated with elevated lung macrophage numbers. These findings support a model in which hyperoxia-induced alterations in Clara cell function influence lung innate immune function through effects on immunomodulatory proteins. Studies to determine the mechanism(s) by which CCSP alterations affect SCGBs, ANXA1, and innate immune responses in BPD are warranted.